2006
DOI: 10.2166/wh.2006.016
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne outbreaks reported in the United States

Abstract: Epidemic waterborne risks are discussed in this paper. Although the true incidence of waterborne illness is not reflected in the currently reported outbreak statistics, outbreak surveillance has provided information about the important waterborne pathogens, relative degrees of risk associated with water sources and treatment processes, and adequacy of regulations. Pathogens and water system deficiencies that are identified in outbreaks may also be important causes of endemic waterborne illness. In recent years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(132 citation statements)
references
References 20 publications
(18 reference statements)
1
122
0
9
Order By: Relevance
“…While irrigation is often the most important contributor to national water consumption (Jiménez and Asano, 2008), because of global change the world is facing increasing limitations of water resources (IPCC, 2012) in terms of quantity (Lazarova and Asano, 2005) and quality (Craun et al, 2006).…”
Section: Water Resources Of Diminishing Quality and Quantitymentioning
confidence: 99%
“…While irrigation is often the most important contributor to national water consumption (Jiménez and Asano, 2008), because of global change the world is facing increasing limitations of water resources (IPCC, 2012) in terms of quantity (Lazarova and Asano, 2005) and quality (Craun et al, 2006).…”
Section: Water Resources Of Diminishing Quality and Quantitymentioning
confidence: 99%
“…Soils under no-till crop management often have more continuous flow channels (macro pores) than tilled soils [79][80][81], and this may contribute to the rapid movement of injected manure to the subsurface drains.Bacterial contamination of drainage effluent was reported to be most likely in: (a) artificially drained, wet soils; (b) soils receiving high rates of liquid manure; and (c) soils that demonstrated preferential flow [82]. Several studies [77,[83][84][85][86] reported that the application of liquid manure to drained fields resulted in elevated levels of nutrients and bacteria in the receiving waters compared to sites where liquid manure was not applied.…”
Section: Association Of Biosolids and Manure Application With Microbimentioning
confidence: 99%
“…MST study on recreational water contamination in southeastern Lake Huron demonstrated that the dominant source of E. coli in lake water samples was agriculture, which supplied about 60% of the bacteria to the lake, whereas human sources provided only about three percent [87]. In addition, one study carried out on the South Shore Beach in Milwaukee concluded that the high E. coli levels were from local sources of pollution and were rarely affected by regional contamination events such as sewage overflows [88].…”
Section: Association Of Biosolids and Manure Application With Microbimentioning
confidence: 99%
“…In the US, 3-10 billion gallons of untreated wastewater are discharged annually. These "sanitary sewer overflows" as a result of blockages Sources of waterborne disease outbreaks shifting to distribution systems [1].…”
Section: Figurementioning
confidence: 99%